Risk Factors and Outcomes of Nontuberculous Mycobacterial Disease among Rheumatoid Arthritis Patients: A Case-Control study in a TB Endemic Area - Liao, Tsai-Ling (Sci Rep, 2016)
Increasing evidence indicates that the risk of nontuberculous mycobacteria (NTM) disease is elevated in patients with rheumatoid arthritis (RA). However, the risk factors and outcomes for NTM disease among RA patients remain unclear. We conducted a case-control study and estimated odds ratios (ORs) for RA patients with NTM disease according to comorbidities and anti-rheumatic medications by using conditional logistic regression. Prior tuberculosis history (adjusted OR (aOR) =5.58, p < 0.001), hypertension (aOR = 2.55, p = 0.013), diabetes mellitus (aOR = 3.31, p = 0.005), interstitial lung disease (aOR = 8.22, p < 0.001), chronic obstructive pulmonary disease (aOR = 8.59, p < 0.001) and exposure to oral corticosteroids in a dose-dependent manner (5− < 10 mg/day aOR = 2.51, P(trend) = 0.007) were associated with a significantly increased risk of NTM disease in RA patients. The predominant species causing NTM disease in RA patients was Mycobacterium intracellulare (46.0%). Most NTM isolates were resistant to the majority of the antibiotics that are currently available, which maybe caused treatment failure; hospitalization and mortality are increased. To prevent and treat NTM disease efficiently, we suggested that it is important to monitor the development of NTM disease in RA patients receiving therapy with corticosteroids, particularly in those with predisposing factors.